Tuji jezik v prvem triletju waldorfske osnovne šole: stališča staršev iz treh držav - Mithans, Monika (Revija za elementarno izobraževanje, 2013)
Foreign Language in the First Cycle of Waldorf Primary Education – Viewpoints of Parents from Three Countries. This paper seeks to present the viewpoints of Slovenian, Austrian, and German parents whose children attend Waldorf primary schools, about learning foreign languages at the primary level. The first section of the paper outlines the main characteristics of learning and teaching foreign languages in Waldorf primary schools and compares the syllabus for the first foreign language in Austria, Slovenia, and Germany. Further on, the paper focuses on the results of an empirical research which involved 215 parents. The results showed that parents who could directly observe the effects of learning a foreign language in childhood were more inclined to it. They were also familiar with the benefits of learning a foreign language for a child. Also, the majority of them agreed that learning second languages was easier for children, and they did not think it had any adverse impact on the mother tongue or the child’s personality.
Keywords: learning languages at primary level; Waldorf pedagogy; parent opinion